Konsep Pendidikan Akhlak Studi Komparasi Pemikiran Imam Al-Ghazali dan Buya Hamka - Furqon Hakim; Imam Syafe'i; Erjati Abbas (Attractive : Innovative Education Journal, 2024)
The purpose of this study is to determine how the concept of akhlak education the perspective of Imam al-Ghazali and Buya Hamka is related to educators and methods in akhlak education. In this study, the type of library research is collecting data or scientic papers that aim to have research objects or data collection that is library-based or studies carried out to solve a problem that is basically based on critical and in-depth studies of in-depth library materials. The data sources used are primary data sources and secondary data sources. The data analysis technique in this study indicates that those who must be responsible for akhlak education according to Buya Hamka: Parents, Teachers and Society, for the method of moral education according to Hamka, namely, al-hikmah, al-mau’izah hasanah, jadilhum billati hiya ahsan. While and educator in akhlak education according to Imam al-Ghazali should have a personality that can reflect religious teachings. According to Imam al-Ghazali, akhlak education methods include the method of role modeling, habituation, advice, attention and punishment.